100 volunteers from UMPSA, TMB, SWCorp, and Alam Flora clean Cherok Paloh Beach while plogging - Norul Fadilah, Abdullah (UMPSA, 2024)
KUANTAN, 23 August 2024 – A total of 100 participants, including staff and students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Tanah Makmur Berhad (TMB), SWCorp Pahang Branch, and Alam Flora, participated in the UMPSA x TMB Plogging Programme held recently at Pantai Cherok Paloh, Kuantan.